Attitudes and behaviors of the students of the Technical University of Palestine - Khadouri - Ramallah branch from the point of view of the lecturers - Nassar, Ahmed Salim Hussein (Journal of Educational and Psychological Sciences, 2020)
The aim of the study was to know the attitudes and behaviors of female students at the Palestinian Technical University Khadouri - Ramallah Branch in all areas of the educational process and to determine the level of practice of the university lecturers for the methods of behavior modification and change of attitudes in the students. The researcher used the analytical descriptive method (a questionnaire applied to a sample of 29 lecturers). They were randomly selected. The data were processed using the SPSS program. The study revealed that the attitudes and behaviors of university students from the point of view of the lecturers are positive and good. Where the average (3.54) of (5), as a result of the use of lecturers of modern methods to modify the behavior of students, and at the level of domains the first field (relations) on the average (3.77), followed by the fifth area (activities) On average (3.64), the third area (environment) obtained a general average (3.39). The second field (education) received a general average (3.28), and the fourth field (attendance) obtained a general average (3.13), and the results of the study showed no statistically significant differences due to variable years of experience, The study also recommended that lecturers be more committed to the methods of attunement and leniency, show empathy for students, and provide material and moral incentives for female students, as well as the absence of significant differences in gender variables (male and female). Proficiency in both the scientific and behavioral aspects of the university administration, as recommended The study aims to invest the art to enhance the positive behavior of the students.